2021
DOI: 10.3389/fpsyg.2021.614469
|View full text |Cite|
|
Sign up to set email alerts
|

Social Innovation for Food Security and Tourism Poverty Alleviation: Some Examples From China

Abstract: The COVID-19 pandemic has brought hunger to millions of people around the world. Social distancing measures coupled with national lockdowns have reduced work opportunities and the overall household incomes. Moreover, the disruption in agricultural production and supply routes is expected to continue into 2021, which may leave millions without access to food. Coincidentally, those who suffer the most are poor people. As such, food security and tourism poverty alleviation are interlinked when discussing social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…The environment-related effects of food production factors on nutrient supply addressed in the discussion should be further investigated. As demonstrated by many scholars [ 9 , 14 , 179 , 180 ], climate change, poor natural conditions, and fragile ecologies in many least-developed and developing countries make it difficult to combat malnutrition and simultaneously follow sustainable farming practices. For ensuring long-term food and nutritional security across the developing world, future studies must differentiate nutrient supply drivers between income patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment-related effects of food production factors on nutrient supply addressed in the discussion should be further investigated. As demonstrated by many scholars [ 9 , 14 , 179 , 180 ], climate change, poor natural conditions, and fragile ecologies in many least-developed and developing countries make it difficult to combat malnutrition and simultaneously follow sustainable farming practices. For ensuring long-term food and nutritional security across the developing world, future studies must differentiate nutrient supply drivers between income patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Lower incomes degrade dietary choices [ 8 ], as do agricultural production disruptions and food chain breakups [ 14 ]. In response to a degrading food security situation, people are forced to compromise on the nutritional quality of the food they consume, as well as reduce consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the role of social innovation in food redistribution activities, we identified several future research directions, as shown in Supplementary Table S2. First, existing studies (Huang and Tsai, 2021;Lombardi and Costantino, 2020;Sutinen and Narvanen, 2021) realized that the key to maximizing the performance of food redistribution activities is to build connections between the 'wasted places' and the 'needed places' through deploying different social innovation measures, such as online markets and online food-sharing communities. However, the performance of the measures adopted to tackle the connectivity gaps appears to have been largely ignored by the extant literature (De los Mozos et al, 2020).…”
Section: Food Redistribution Rescue Donation and Sharing-related Reco...mentioning
confidence: 99%
“…It is critical to implement strategies that cut across organizational, sectoral, or disciplinary boundaries in order to trigger the awareness of the whole society of the imperative to reduce FW. Particularly, from the social innovation perspective, initiatives such as compelling new social relationships and combining existing elements seem to be the most effective ways to reduce FW (Huang and Tsai, 2021). Recent articles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Food security is an important strategic issue concerning China's economic development and social stability. As a country with a large population in the world, China should attach great importance to food security at all times [ 1 , 2 ]. Since the beginning of the new century, the central government has successively issued no.…”
Section: Introductionmentioning
confidence: 99%